Boundary extension of mappings that satisfy the Poletsky inverse inequality in terms of prime ends - Sevost’yanov , E. A. (Ukrains’kyi Matematychnyi Zhurnal, 2021)
УДК 517.5 For mappings with branching points that satisfy the Poletsky inverse inequality, we obtain some results related to their continuous boundary extension in terms of prime ends. Under certain conditions, the specified classes of mappings are also equicontinuous in the closure of a given domain.